IDENTIFIKASI PENANDA ISOZIM PER-7, PER-8, DAN RAPD OB17375 PADA KELAPA GENJAH SALAK (GSK) DAN BEBERAPA HASIL SILANGANNYA DENGAN KELAPA DALAM - Runtunuwu, Semuel D.; Lengkong, Eddy F. (EUGENIA, 2005)
ABSTRACT Runtunuwu, S.D. and E.F. Lengkong. 2005. Identification of Isozyme Markers (PER-7, PER-8, and RAPD OBI7375) of Dwarf Salak Coconut (GSK) and its Tall Hibrids. Eugenia 11 (1): 8-17. The objective of this research was to identify PER-7 and PER-8 isozymes, and OB17 375 RAPD as molecular markers for resistance to NF Phytophthora disease in Genjah Salak (GSK) dwarf coconut and its several hybrids with Tall coconut at The Research Institute for Coconut and Palmae (RICP) Manado. Coconut resistance to NF Phytophthora disease was determined based on disease lesion size of inoculated coconut fruits at 7 days after inoculation. PER-7 and PER-8 isozymes marker were identified using horizontal starch gel electrophoresis, and OB17375 RAPD marker was identified based on polymerase chain reaction (PCR) using kit B number 17 primer (Operon Technologies, California). PER-7 isozyme marker could be used to select GSK x DTA (Dalam Tenga) and GSK x RLT (Rennell Tall) hybrid coconuts that resistant to NF Phytophthora disease. PER-7 isozyme without OB17375 markers (PER-7/-) could be used to select resistant GSK x WAT (West African Tall) hybrid coconut to the disease. Keywords: Isozymes, RAPD, Molecular marker, Phytophthora disease, coconut